Revisiting Edward Said`s Self-Representation in Susan Abulhawa`s Mornings in Jenin - Norah Hasan Alqahtani (Taez University, 2024)
Edward Said advocated for Palestinians to tell their own stories, emphasizing the need of self-representation in literature, politics, and cultural discourse. He believed that by reclaiming their narratives, Palestinians might combat inaccurate portrayals, counter negative stereotypes, and assert their autonomy in constructing their history and identity. This study argues that Susan Abulhawa's Mornings in Jenin echoes Said's call for self-representation by using storytelling to communicate a Palestinian perspective. Abulhawa's method provides an alternative narrative to external portrayals, which may perpetuate misunderstandings or oversimplify complex reality. This study focuses exclusively on Edward Said's concept of self-representation while examining Susan Abulhawa's Mornings in Jenin. The question was raised using a postcolonial methodology. The data for the study was obtained from Susan Abulhawa's novel Mornings in Jenin, which was published by Bloomsbury Publishing in 2010. So, this study investigates the Palestinian perspective on the conflict as a decolonial strategy aimed at developing a political platform for Palestinians through a focus on their experiences and struggles under Israeli occupation. In sum, the author`s narrative contributes to a broader conversation on Palestinian identity, dispossession, and resistance.